Corporate Social Responsibility and Pro-Peace Practices in Colombia - Perdomo-Ortiz, Jesús; Villa Castaño, Lida Esperanza; Dueñas Ocampo, Sebastián (Cuadernos de Administración, 2017)
This paper explores the thesis associating the adoption of Corporate Social Responsibility models with implementing Pro-Peace practices in scenarios of conflict and post-conflict. This work is carried out under qualitative focus and exploratory scope. Four interviews were applied to large companies who have adopted Corporate Social Responsibility models and two interviews to Associations promoting Corporate Social Responsibility in Colombia. Evidence supporting this thesis was found and its understanding was dug into when considering that Corporate Social Responsibility, as a concept, has migrated towards Creating Shared Value and Business Sustainability. This study bears the limitations associated to determining a theoretical sample and the bias of selection it implies. From this research is derived that if companies in Colombia wish to promote Pro-Peace practices, they must become involved in management models based on Corporate Social Responsibility.